2007
DOI: 10.1364/josaa.25.000190
|View full text |Cite
|
Sign up to set email alerts
|

Gestalt and phenomenal transparency

Abstract: Phenomenal transparency is commonly studied by using a stimulus configuration introduced by Metelli: a bipartite patch, divided into equal left and right halves is overlaid with a smaller, concentric bipartite patch, divided along the same line. Observers are instructed to report either a transparent patch over an opaque bipartite field or a mosaic of four opaque patches. We show theoretically and empirically that these are only two of five generic perceptual categories, namely, transparent patch, transparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 17 publications
(23 reference statements)
1
22
0
Order By: Relevance
“…In a previous publication (Koenderink et al 2008) we have shown that certain conditions formulated by Metelli indeed account for virtually all our data, but only if certain additional constraints are satisfied. The Metelli conditions (Metelli 1970) can be shown to be low-order approximations to the predictions of physics (Kubelka 1954;Kubelka and Munk 1934) of stacks of turbid sheets illuminated from the viewing direction.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In a previous publication (Koenderink et al 2008) we have shown that certain conditions formulated by Metelli indeed account for virtually all our data, but only if certain additional constraints are satisfied. The Metelli conditions (Metelli 1970) can be shown to be low-order approximations to the predictions of physics (Kubelka 1954;Kubelka and Munk 1934) of stacks of turbid sheets illuminated from the viewing direction.…”
supporting
confidence: 51%
“…The additional categories are:`h ole'' öthe impression is of a large translucent sheet with a small square aperture that overlays a bipartite background and``left'' or``right'' ö the impression of a vertically extended translucent rectangle that covers a background consisting of a large square with smaller centre square of different luminance, on either the left or the right. The former (``hole'') experiences have been reported by us in a previous communication (Koenderink et al 2008). The latter (``left'' or``right'') experiences have been reported earlier (Beck and Ivry 1988), though they don't figure prominently in the literature.…”
mentioning
confidence: 64%
“…As others have found before us, the limiting conditions for the more physically realistic models were rather similar to Metelli's. Hence when a Metelli violation occurred, typically that setting also violated the Kubelka-Munk model (see also [20].) The intuitive explanation for the similar results is that sign shifts in the contrast difference between P and Q and A and B usually do not survive either model.…”
Section: Kubelka Munk Limitsmentioning
confidence: 77%
“…In line with modern treatments of the transparency problem (e.g., Beck, Prazdny, & Ivry, 1984;Koenderink, van Doorn, Pont, & Richards, 2008;Metelli, 1970), two kinds of psychophysical dependence may be hypothesised among those properties. One kind involves the luminance L 1,j of any internal region R 1,j in the stimulus, the apparent transparency T and whiteness W of the figure surface A in the percept, the apparent whiteness W j of the background surface B j , and the apparent intensity I of the illumination in the scene, which is expressed by the equation…”
Section: Original Contributions -Originalbeiträgementioning
confidence: 95%